2021
DOI: 10.1038/s41598-021-84566-2
|View full text |Cite
|
Sign up to set email alerts
|

SNP-based analysis reveals unexpected features of genetic diversity, parental contributions and pollen contamination in a white spruce breeding program

Abstract: Accurate monitoring of genetic diversity levels of seedlots and mating patterns of parents from seed orchards are crucial to ensure that tree breeding programs are long-lasting and will deliver anticipated genetic gains. We used SNP genotyping to characterize founder trees, five bulk seed orchard seedlots, and trees from progeny trials to assess pollen contamination and the impact of severe roguing on genetic diversity and parental contributions in a first-generation open-pollinated white spruce clonal seed or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…The main advantages of SNP markers over traditional microsatellites include their availability (SNP resources have been published for most conifer species, including maritime pine, Plomion et al 2016), low genotyping error rate, and the possibilities for multiplexing and automation of genotyping for high-throughput analyses. However, only a few studies to date implemented SNP markers to study pollen contamination in forest trees (Galeano et al 2021;Hall et al 2020;Suharyanto et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantages of SNP markers over traditional microsatellites include their availability (SNP resources have been published for most conifer species, including maritime pine, Plomion et al 2016), low genotyping error rate, and the possibilities for multiplexing and automation of genotyping for high-throughput analyses. However, only a few studies to date implemented SNP markers to study pollen contamination in forest trees (Galeano et al 2021;Hall et al 2020;Suharyanto et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Plomion et al (2005) subsequently used nuclear microsatellites and revealed similar high pollen contamination rates in second-generation seed orchards (32% to 81%). Medium-to-high levels of pollen contamination have been reported in conifer species: 28% in Pinus thumbergii (Suharyanto et al 2012), 49% in Cryptomeria japonica (Moriguchi et al 2010), 12-35% in Pseudotsuga menziesi (Korecký and El-Kassaby 2016; Slavov et al 2005), 27% in Picea glauca (Galeano et al 2021), 58% in Picea abies (Dering et al 2014), 5-52% in Pinus sylvestris (Funda et al 2015; Torimaru et al 2009), and 86% in Pinus brutia (Kaya et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The main advantages of SNP markers include their high repeatability (Jones et al, 2007), the possibilities for multiplexing and automation of genotyping which makes them cost-effective for high-throughput analyses. In most species, SNP markers have become a tool of choice for parentage analyses (Flanagan & Jones, 2019) but only a few studies to date implemented them to estimate pollen contamination in forest trees (Galeano et al, 2021;Hall et al, 2020;Suharyanto et al, 2012).…”
Section: Snp Markers: An Efficient Tool To Study Pollen Contamination...mentioning
confidence: 99%
“…White spruce ( Picea glauca (Moench) Voss) is one of the most widely distributed tree species in Canada, and with tree improvement programs across the country ( Galeano et al., 2021 ). In Alberta, Canada, improvement programs for white spruce mainly use open-pollinated material, however, this strategy is not sufficient to explore the full potential of productivity of white spruce plantations ( Flewelling, 2008 ; Sklar, 2012 ; FGRMS, 2016 ; Government of Alberta, 2018 ; Galeano et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…White spruce ( Picea glauca (Moench) Voss) is one of the most widely distributed tree species in Canada, and with tree improvement programs across the country ( Galeano et al., 2021 ). In Alberta, Canada, improvement programs for white spruce mainly use open-pollinated material, however, this strategy is not sufficient to explore the full potential of productivity of white spruce plantations ( Flewelling, 2008 ; Sklar, 2012 ; FGRMS, 2016 ; Government of Alberta, 2018 ; Galeano et al., 2021 ). In order to advance improvement in white spruce, the adoption of controlled crosses needs to be considered as it typically results in better productivity than open pollination in most cases, and this approach has been the backbone of plant domestication ( Leakey, 2017a ).…”
Section: Introductionmentioning
confidence: 99%